Characterization of NOD-like receptor-based molecular heterogeneity in glioma and its association with immune micro-environment and metabolism reprogramming - Lu, Chunlin; Ma, Huihao; Wang, Jie; Sun, Fei; Fei, Mingyang; Li, Ying; Liu, Jing; Dong, Bin (Frontiers in Immunology, 2025)
Background and purposeThe characteristics and role of NOD-like receptor (NLR) signaling pathway in high-grade gliomas were still unclear. This study aimed to reveal the association of NLR with clinical heterogeneity of glioblastoma (GBM) patients, and to explore the role of NLR pathway hub genes in the occurrence and development of GBM.MethodsTranscriptomic data from 496 GBM patients with complete prognostic information were obtained from the TCGA, GEO, and CGGA databases. Using the NMF clustering algorithm and the expression profiles of NLR genes, these 496 GBM patients were classified into different clinical subtypes. The pathway activity of NLR and the immune micro-environment characteristics were then compared between these subtypes. A novel and accurate NLR expression profile-based prognostic marker for GBM was developed using LASSO and COX regression analysis.ResultsBased on the NLR gene expression profile, GBM patients were accurately divided into two clinical subtypes (C1 and C2) with different clinical outcomes. The two groups of patients showed different immune microenvironment characteristics and metabolic characteristics, which might be the potential reason for the difference in prognosis. Differential expression and enrichment analyzes revealed intrinsic gene signature differences between C1 and C2 subtypes. Based on the differential expression profiles of C1 and C2, prognostic molecular markers related to NLR were developed. The AUC value of the 3-year ROC curve ranged from 0.601 to 0.846, suggesting its potential clinical significance. Single-cell sequencing analysis showed that the NLR gene was mainly active in myeloid cells within GBM. The random forest algorithm identified the crucial role of TRIP6 gene in NLR pathway. Molecular biology experiments confirmed that TRIP6 was abnormally overexpressed in GBM. Knockdown of TRIP6 gene can significantly inhibit the proliferation and migration ability of GBM cells.ConclusionThe NLR signaling pathway plays a critical role in regulating immune microenvironment and metabolism reprogramming of GBM. TRIP6 is a potential hub gene within the NLR pathway and affects the malignant biological behavior of GBM cells.